2015
DOI: 10.4155/fso.15.13
|View full text |Cite
|
Sign up to set email alerts
|

Role of STAT3 pathway in genitourinary tumors

Abstract: The STAT3 is often dysregulated in genitourinary tumors. In prostate cancer, STAT3 activation correlates with Gleason score and pathological stage and modulates cancer stem cells and epithelial-mesenchymal transition. In addition, STAT3 promotes the progression from carcinoma in situ to invasive bladder cancer and modulates renal cell carcinoma angiogenesis by increasing the expression of HIF1α and VEGF. STAT3 is also involved in the response to tyrosine kinase inhibitors sunitinib and axitinib, in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 84 publications
1
35
0
Order By: Relevance
“…30 STAT3 plays a role in regulating the expression of transcriptional factors that drive EMT and modulating cytoskeleton dynamic during the initiation stage of the EMT. 38 In addition, we also observed that treatment of cells with GSSG liposomes caused apoptosis in these cells. 30 …”
Section: Discussionmentioning
confidence: 61%
“…30 STAT3 plays a role in regulating the expression of transcriptional factors that drive EMT and modulating cytoskeleton dynamic during the initiation stage of the EMT. 38 In addition, we also observed that treatment of cells with GSSG liposomes caused apoptosis in these cells. 30 …”
Section: Discussionmentioning
confidence: 61%
“…Signal transduction and activators of transcription factor (STAT) 3, a member of the STAT family, is frequently regarded as an oncogene [4][5][6]. STAT3 can be activated via phosphorylation events within the Janus kinase-STAT, producing tyrosine or serine phosphorylated STAT3 (p-STAT3) [7,8]. p-STAT3 is able to increase the expression levels of certain target genes, including vascular endothelial growth factor (VEGF), Cyclin D1 and Bcl-xL, etc [9][10][11][12].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…'s case report demonstrating a need for more collaboration to ensure literature reviews are comprehensive [9], a new generic model to help the development of applications for clinical decision-making created by Tibor van Rooij and colleagues [10], an examination of the potential uses of the STAT3 pathway in genitourinary tumors [11], and, finally, a research article examining the potential of extracellular embryo genomic DNA for genotyping applications [12]. This content is merely a snapshot of our excellent articles, and once again we thank all of our authors for their efforts throughout the year.…”
Section: Content Highlights From 2015mentioning
confidence: 99%